Penggunaan Media Sosial Youtube dalam Motivasi Siswa Belajar Passing Permainan Sepakbola pada Masa Pandemi - Suryana Nasution, Nana (Jurnal Literasi Olahraga, 2022)
The purpose of this research is to find out whether learning using Youtube Social media can motivate students and increase students' knowledge about learning to pass the soccer game. This research is a type of quantitative research (non-experimental) with a descriptive approach. In this study using a survey method with data collection techniques with a questionnaire. From the results of the study, it was known that the use of Youtube Social Media in Motivating Students to Learn Passing Football Games during the Covid-19 Pandemic, which stated the "very good" category with a percentage of 6.5%, the "Good" category with a percentage of 25.8%, the "Medium" category. ” with a percentage of 35.5%, the category of “Less” with a percentage of 25.8%, and the category of “very Poor” with a percentage of 6.5%. So it can be concluded that the use of Youtube social media in motivating students to learn to pass soccer games during a pandemic is in the good or medium category.